GAMIFICATION IN EDUCATION: TRANSFORMING LEARNING TO BE MORE FUN AND EFFECTIVE - Perengki Yansah; Ismaul Fitroh; Moh. Imron Rosidi (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Gamification in education is an innovative approach that applies game elements and principles to the learning process. Its main goal is to increase student engagement and motivation, thus creating a more enjoyable and effective learning experience. In its implementation, gamification incorporates technology to provide an interactive learning environment that focuses on achievement and skill development. While it offers many benefits, gamification implementation also faces challenges, including the need for proper planning and adaptation according to the specific needs of the curriculum. This shows that when implemented correctly, gamification can be a powerful tool to advance pedagogy and improve student academic outcomes.